(3GdJMdjd GdESJQGJjLj aj EYGOI gfOSI GdYedjGJ GdEOGQjI (B/s - (3GdUQGjQI, GSeGYjd eMeOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3NdajI GdOQGSI heTcdJgG , GdGWGQ GdfXQj hGdOQGSGJ GdSGHbI , GdefgLjI hGdJUeje , YQV GdfJGFL hefGbTJgG hGdJhUjGJs
(3GdeQGLY U(B.119s
Keywords: (3GdEOGQIs; (3GdEOGQI GdYdejIs; (3GdEOGQI GdgfOSjIs; (3JfXje hEOGQIs